Chronic high-fat diet-induced obesity in gerbils increases pro-inflammatory cytokines and mTOR activation, and elicits neuronal death in the striatum following brief transient ischemia. (December 2018) - Song, Minah; Ahn, Ji Hyeon; Kim, Hyunjung; Kim, Dae Won; Lee, Tae-Kyeong; Lee, Jae-Chul; Kim, Young-Myeong; Lee, Choong-Hyun; Hwang, In Koo; Yan, Bing Chun; Won, Moo-Ho; Park, Joon Ha
Abstract: Recent studies have shown that obesity and its related metabolic dysfunction exacerbate outcomes of ischemic brain injuries in some brain areas, such as the hippocampus and cerebral cortex when they are subjected to transient ischemia. However, the impact of obesity in the striatum after brief transient ischemia has not yet been addressed. The objective of this study was to investigate effects of obesity on neuronal damage and inflammation in the striatum after transient ischemia and to examine the role of mTOR which is involved in the pathogenesis of metabolic and neurological diseases. Gerbils were fed with normal diet (ND) or high-fat diet (HFD) for 12 weeks and subjected to 5 min of transient ischemia. HFD-fed gerbils showed significant increase in body weight, blood glucose level, serum triglycerides, total cholesterol and low-density lipoprotein cholesterol without affecting food intake. Neuronal death/loss in the HFD-fed gerbils occurred in the dorsolateral striatum 2 days after transient ischemia, and neuronal loss was increased 5 days after transient ischemia, although no neuronal loss was observed in ND-fed gerbils at any time after transient ischemia. The HFD-fed gerbils showed hypertrophied microglia and further increased expressions of tumor necrosis factor-alpha, interukin-1beta, mammalian target of rapamycin (mTOR) and phosphorylated-mTOR during pre- and post-ischemic phases compared with the ND-fed gerbils. Additionally, we found that treatment with mTOR inhibitor rapamycin in the HFD-fed gerbils significantly attenuated transient ischemia-induced neuronal death in the dorsolateral striatum. These findings reveal that chronic HFD-induced obesity results in severe neuroinflammation and significant increase of mTOR activation, which could contribute to neuronal death in the stratum following 5 min of transient ischemia. Especially, abnormal mTOR activation would play a key role in mediating obesity-induced severe ischemic brain injury. Highlights: High-fat diet (HFD) feeding for 12 weeks induces obesity in gerbils. HFD feeding elicits neuronal death in the striatum after brief transient ischemia (bTI). HFD feeding exacerbates inflammation in the striatum after bTI. HFD feeding increases mTOR activation in the striatum after bTI. Rapamycin, a mTOR inhibitor, attenuates bTI-induced neuronal death under obesity.